Thia-Bridged Triarylamine[4]helicene-Functionalized Polynorbornenes as Redox-Active pH-Sensitive Polymers - Lupi, Michela; Menichetti, Stefano; Stagnaro, Paola; Utzeri, Roberto; Viglianisi, Caterina (Synthesis, 2021)
A series of thia-bridged triarylamine[4]helicene-functionalized polynorbornenes P1, P2, and P3 were synthesized via ring-opening metathesis polymerization (ROMP). The polymers obtained undergo a reversible one-electron oxidation, in both solution and solid state, responding to the pH changes in the surrounding medium showing a clear reversible electrochromic behavior.
Keywords: hetero[4]helicenes; radical cations; ROMP; pH-sensitive polymers; redox polymers; electrochromic polymers